Sonophotocatalytic degradation of sodium diclofenac using low power ultrasound and micro sized TiO2 - Meroni, D. (Elsevier B.V., 2020)
The nonsteroidal anti-inflammatory drug sodium diclofenac (DC) is an emerging water pollutant which resists conventional wastewater treatments. Here the sonophotocatalytic degradation of DC was carried out using micrometric TiO2 (both pristine and Ag-decorated), UV-A irradiation and 20 kHz pulsed ultrasound. Sonophotocatalytic tests were compared with photolysis, sonolysis, sonophotolysis, sonocatalysis and photocatalysis data performed in the same conditions. A synergy index of over 2 was determined for tests with pristine TiO2, while values close to 1.3 were observed for Ag-TiO2. Reaction intermediates were studied by HPLCâMS, showing degradation mechanisms activated by hydroxyl radicals. Similar pathways were identified for photocatalytic and sonophotocatalytic tests, although the latter led to more oxidized compounds. Different reactor configurations (static and dynamic set ups) were studied. Sequential and simultaneous application of UV light and ultrasound led to similar performance. The role of water matrix was investigated using ultrapure and drinking water, showing marked detrimental effects of electrolytes on the DC degradation. Overall, the combined treatment proved more efficient than photocatalysis alone especially in demanding working conditions, like in drinking water matrices. Â© 2020 Elsevier B.V.